Ternary lithium ion battery positive electrode material, preparation method thereof and lithium ion battery
By using saturated carbon dioxide solution to form a Li2CO3 layer on the positive electrode material of lithium-ion battery and performing metal ion exchange, the problem of uneven coating of the positive electrode material is solved, and the electrochemical performance and cyclic stability of the material are significantly improved.
Patent Information
- Application Number
- CN202411769501.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-04
AI Technical Summary
The uneven coating of the positive electrode materials of existing lithium-ion batteries leads to problems such as side reactions, lattice oxygen release, irreversible phase change and stress-induced cracking under high pressure, affecting the cycle stability and energy density of the battery.
The monohydrate matrix material is processed by saturated carbon dioxide solution, and a highly uniform Li2CO3 layer is formed through the orientation of CO2 bubble nucleation, and various metal elements are doped with the aid of ion exchange to achieve uniform metal ion compound coating.
Through this method, defects on the surface of the material can be effectively protected, highly uniform coating can be achieved, and the electrochemical performance and cyclic stability of the material can be improved.
Smart Images

Figure CN119612614A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium batteries, and in particular to a ternary lithium-ion battery positive electrode material and a preparation method thereof and a lithium-ion battery. Background Art
[0002] At present, the positive electrode determines the overall energy density of the battery. One of the development trends of high energy density positive electrodes is to increase the upper cutoff voltage to increase the discharge depth, thereby achieving high capacity. However, positive electrode materials have a series of problems under high pressure, including side reactions, lattice oxygen release, irreversible phase change and stress-induced cracking, etc. These problems are closely related to the stability of the positive electrode surface. The existing method to solve such problems is to modify the surface of the positive electrode active material. Traditional coating methods, such as sol-gel, hydrothermal treatment and mechanical ball milling, are difficult to ensure uniformity. Atomic layer deposition (ALD) technology can achieve atomic scale regulation and construct a uniform coating, but its high cost hinders its industrial application.
[0003] The existing invention patent with patent publication number CN109742346A discloses a Si / Al co-coated nickel-cobalt-manganese lithium-ion battery positive electrode material and a preparation method thereof. The coated Si / Al can effectively prevent the diffusion of F anions, reduce impedance, inhibit the decomposition of the electrolyte on the coating layer, improve the rate performance of the material, and enhance the cycle stability of the material. However, the preparation method adopts a simple high-mixer physical mixing method for coating, and it is difficult for the coating material to form a uniform coating layer on the surface of the material, and ineffective coating is easily formed locally.
[0004] And the invention patent with the existing patent publication number CN112103496A discloses a high-nickel ternary positive electrode material and its preparation method. Under the implementation of this coating method, Sr is coated in a molten state or enriched on the surface of the material without a coating layer, and the concentration decreases from the outside to the inside, forming a gradient doping, and the material has high capacity and good cycle stability in a high-voltage system. However, the coating process is cumbersome, especially the secondary Sr coating process. The first Sr coating still adopts the method of physical mixing of a high mixer, and the uniformity of the coating is difficult to guarantee. Although the second Sr coating process is objectively carried out to make up for it, it undoubtedly increases the cumbersomeness of the process. At the same time, the second Sr coating is carried out in a wet system, which makes the operation of the first Sr coating more unnecessary. Coating in a wet system is microscopically ion-level coating, and the uniformity of the coating is better than that of dry coating, but the non-anchoring of the coated ions on the surface of the material makes the surface coating also have certain defects. Summary of the invention
[0005] The main purpose of the present invention is to provide a ternary lithium-ion battery positive electrode material and a preparation method thereof and a lithium-ion battery, aiming to solve the technical problem of uneven coating of existing positive electrode materials.
[0006] To achieve the above object, the present invention provides a method for preparing a positive electrode material for a ternary lithium-ion battery, the method comprising the following steps:
[0007] Step 1, mixing a preset amount of ternary precursor and a Li source and sintering them in an oxygen-containing atmosphere at 700-1000° C. for 8-24 hours, crushing and sieving to obtain a sintered matrix material 1, wherein the ternary precursor is Ni x Co y Mn (1-x-y) (OH) 2 , 0.5≤x≤0.98, 0.01≤y≤0.3, x+y<1, the molar ratio of the lithium element in the Li source to the total molar ratio of the nickel, cobalt and manganese elements in the ternary precursor is (1.02-1.08):1;
[0008] Step 2: adding the monoalkyl matrix material 1 obtained in step 1 to a saturated carbon dioxide solution and stirring for 1 to 2 hours to form a Li 2 CO 3 layer, filtering, drying and sieving to obtain powder material 2;
[0009] Step 3, adding the powder material 2 to a soluble salt solution containing metal ions and stirring and mixing for 1 to 2 hours, filtering, drying and sieving to obtain a preliminary coating material 3, wherein the weight ratio of the metal ions to the powder material 2 is (0.0002 to 0.006): 1;
[0010] Step 4, sintering the preliminary coating material 3 in an oxygen-containing atmosphere at 300-800° C. for 1-6 hours, and obtaining a ternary lithium-ion battery positive electrode material coated with a metal ion compound after cooling.
[0011] Optionally, in step 1, Li source is Li 2 O, LiOH, Li 2 C 2 O 4 and Li 2 CO 3 At least one of .
[0012] Optionally, in step 2, the saturated carbon dioxide solution includes any one of a saturated carbon dioxide aqueous solution, a saturated carbon dioxide acetone solution, a saturated carbon dioxide methanol solution, and a saturated carbon dioxide ethanol solution.
[0013] Optionally, in step 3, the soluble salt solution includes a nitrate solution.
[0014] Optionally, the metal ions include Li 2 CO 3 Metal ions with low solubility product constants corresponding to the carbonates of metal ions.
[0015] Optionally, the metal ions include at least one of the metal ions corresponding to Mg, Al, Ca, Ba, Fe, Co, Mn, Cu, Zn, Y, Sr, Zr, Ce and La.
[0016] Optionally, the carbon dioxide saturated solution is a saturated carbon dioxide acetone solution, and the Li source is lithium carbonate.
[0017] Optionally, the oxygen-containing atmosphere in steps 1 and 4 contains 20-100% oxygen by volume.
[0018] In addition, in order to achieve the above-mentioned purpose, the present invention also provides a ternary lithium-ion battery positive electrode material, and the ternary lithium-ion battery positive electrode material is prepared according to the preparation method of the ternary lithium-ion battery positive electrode material described in any one of the above items.
[0019] In addition, in order to achieve the above-mentioned purpose, the present invention also provides a lithium-ion battery, which includes the above-mentioned ternary lithium-ion battery positive electrode material.
[0020] Beneficial effects:
[0021] The present invention uses a saturated carbon dioxide solution to treat an alkane matrix material. Based on the orientation of bubble nucleation, the rough surface of the alkane matrix material is CO 2 The top priority sites for bubble nucleation. These local sites with high roughness often have defects and are easily degraded during electrochemical cycling. CO 2 Bubble treatment can effectively coat the vulnerable points of the surface, CO 2 Once bubbles are formed, they interact with the lithium oxide positive electrode to form Li 2 CO 3 layer, further assisted by ion exchange, this highly uniform Li 2 CO 3 The thin layer can be used as a substrate for doping various metal elements at room temperature. 2 CO 3 Transformed into amorphous metal ions to anchor Li 2 CO 3 Layer. The coating method of the present invention can well protect the surface defects of the material. 2 CO 3 The highly uniform coating is achieved under the action of the layer substrate, thereby improving the electrochemical performance of the material. + CO2 Early extraction allows some elements that are difficult to directly exchange ions with the positive electrode to be achieved under mild conditions. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 It is a schematic flow chart of an embodiment of a method for preparing a positive electrode material for a ternary lithium-ion battery of the present invention.
[0023] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION
[0024] It should be understood that the specific embodiments described herein are only used to explain the present invention, and are not used to limit the present invention.
[0025] See also Figure 1 The present invention provides an embodiment of a method for preparing a positive electrode material for a ternary lithium-ion battery, the method comprising the following steps:
[0026] Step 1, mixing a preset amount of ternary precursor and a Li source and sintering them in an oxygen-containing atmosphere at 700-1000°C for 8-24h, crushing and sieving to obtain a sintered matrix material 1. The ternary precursor is Ni x Co y Mn (1-x-y) (OH) 2 , 0.5≤x≤0.98, 0.01≤y≤0.30, x+y<1, the molar ratio of the lithium element in the Li source to the total molar ratio of the nickel, cobalt and manganese elements in the ternary precursor is (1.02-1.08):1, preferably, the Li source is Li 2 O, LiOH, Li 2 C 2 O 4 and Li 2 CO 3 At least one of .
[0027] Step 2, adding the monoalkyl matrix material 1 obtained in step 1 to a saturated carbon dioxide solution and stirring for 1 to 2 hours, filtering, drying and sieving to obtain a powder material 2, wherein the saturated carbon dioxide solution includes any one of a saturated carbon dioxide aqueous solution, a saturated carbon dioxide acetone solution, a saturated carbon dioxide methanol solution, and a saturated carbon dioxide ethanol solution. This step is to form Li on the surface of the monoalkyl matrix material 1. 2 CO 3 layer, which is based on CO 2 The orientation of bubble nucleation makes the rough surface of the sintered matrix material 1 be CO 2 The highest priority for bubble nucleation is CO 2Once bubbles are formed, they interact with the lithium oxide positive electrode to form Li 2 CO 3 layer, and the local sites with high roughness of the alkane matrix material 1 often have defects during the electrochemical cycle and are easily degraded. CO is preferred. 2 The bubbling treatment can effectively coat the fragile points on the surface, so that Li 2 CO 3 Substrate layer.
[0028] Step 3, adding the powder material 2 to a soluble salt solution containing metal ions and stirring and mixing for 1 to 2 hours, filtering, drying and sieving to obtain a preliminary coating material 3, wherein the weight ratio of the metal element to the powder material 2 is (0.0002 to 0.006): 1, the soluble salt solution includes a nitrate solution, and the metal ions are in a ratio of Li 2 CO 3 The metal ion corresponding to the metal ion carbonate with a low solubility product constant is preferably at least one of the metal ions corresponding to Mg, Al, Ca, Ba, Fe, Co, Mn, Cu, Zn, Y, Sr, Zr, Ce and La. In this step, based on the ratio of the metal ion carbonate to Li 2 CO 3 The solubility product constant is low, which can realize the metal ion and Li 2 CO 3 The layer undergoes ion exchange, and the surface Li 2 CO 3 The layer reacts with metal ions to generate more insoluble substances, making the surface Li 2 CO 3 Transformed into amorphous metal ions to anchor Li 2 CO 3 layer, and finally doped various metal elements on the surface of the matrix material. + CO 2 Early extraction allows some elements that are difficult to directly exchange ions with the positive electrode to be achieved under mild conditions, thereby optimizing the coating reaction conditions.
[0029] Step 4, sintering the preliminary coating material 3 in an oxygen-containing atmosphere at 300-800° C. for 1-6 hours, and cooling to obtain a ternary lithium-ion battery positive electrode material uniformly coated with a metal ion compound. The oxygen-containing atmosphere in steps 1 and 4 contains 20-100% oxygen by volume.
[0030] Furthermore, the above preparation process is described below through specific examples.
[0031] Example 1
[0032] Step 1: Weigh Ni at a molar ratio of Li / (Ni+Co+Mn) = 1.02. 0.6 Co 0.1 Mn 0.3 (OH) 2 Precursor and lithium carbonate, then add the precursor and lithium carbonate into a high-speed mixer, sinter the mixture at 940°C for 15h in an atmosphere containing 20% by volume oxygen, naturally cool to 100°C, and then grind and sieve to obtain a sintered matrix material 1.
[0033] Step 2: weigh the alkane matrix material 1 in step 1 and add it to saturated CO 2 The acetone solution was stirred at 500 rpm for 1 h, and after filtering, drying and sieving, the relevant powder material 2 was obtained.
[0034] Step 3, adding the powder material 2 obtained in step 2 to a nitrate solution containing Al and Sr ions for treatment, wherein the weight ratios of Al and Sr elements to the powder material are 0.0006 and 0.0012, respectively, stirring at 500 rpm for 1 hour, filtering, drying and sieving to obtain a preliminary coated material 3.
[0035] Step 4, sintering the preliminary coating material 3 obtained in step 3 at 400° C. for 2 h in an atmosphere containing 50% by volume oxygen, naturally cooling to 100° C., and then sieving to obtain the Sr / Al co-coated positive electrode material 1.
[0036] Make a button cell battery.
[0037] Sr / Al co-coated positive electrode material 1-LiNi 0.6 Co 0.1 Mn 0.3 O 2 It is evenly mixed with conductive agent acetylene black and binder PVDF in a mass ratio of 90:3:7, and an appropriate amount of NMP is added to form a slurry. It is evenly coated on an aluminum sheet, and made into a positive electrode sheet after drying and rolling. Then, a metal lithium sheet is used as the negative electrode to assemble it into a 2032 button battery, and the electrical performance is tested using a blue electric test system (the charge and discharge voltage is 3.0~4.5V).
[0038] Example 2
[0039] Step 1: Weigh Ni at a molar ratio of Li / (Ni+Co+Mn) = 1.06. 0.6 Co 0.1 Mn 0.3 (OH) 2 Precursor and lithium carbonate, then add the precursor and lithium carbonate into a high-speed mixer, sinter the mixture at 940°C for 15h in an atmosphere containing 100% by volume oxygen, naturally cool to 100°C, and then crush and sieve to obtain a sintered matrix material 1.
[0040] Step 2, weigh the monoalkyl base material 1 in step 1, add it to a saturated carbon dioxide aqueous solution, stir at 500 rpm for 1 hour, and obtain the relevant powder material 2 after filtering, drying and sieving.
[0041] Step 3, adding the powder material 2 obtained in step 2 into a nitrate solution containing Sr ions for treatment, wherein the weight ratio of the Sr element to the powder material is 0.0012, stirring at 500 rpm for 1 hour, filtering, drying and sieving to obtain a preliminary coating material 3.
[0042] Step 4: The preliminary coating material 3 obtained in step 3 is sintered at 400° C. for 2 h in a pure oxygen atmosphere, and then naturally cooled to 100° C., and then sieved to obtain the Sr-coated positive electrode material 2.
[0043] Make a button cell battery.
[0044] The Sr-coated positive electrode material 2-LiNi 0.6 Co 0.1 Mn 0.3 O 2 It is evenly mixed with conductive agent acetylene black and binder PVDF in a mass ratio of 90:3:7, and an appropriate amount of NMP is added to form a slurry. It is evenly coated on an aluminum sheet, and made into a positive electrode sheet after drying and rolling. Then, a metal lithium sheet is used as the negative electrode to assemble it into a 2032 button battery, and the electrical performance is tested using a blue electric test system (the charge and discharge voltage is 3.0~4.5V).
[0045] Example 3
[0046] Step 1: Weigh Ni at a molar ratio of Li / (Ni+Co+Mn) = 1.08. 0.7 Co 0.1 Mn 0.2 (OH) 2 Precursor and lithium hydroxide, then add the precursor and lithium hydroxide into a high-speed mixer, sinter the mixture at 700°C for 24 hours in an atmosphere containing 20% by volume oxygen, naturally cool to 100°C, and then crush and sieve to obtain a sintered matrix material 1.
[0047] Step 2: weigh the alkane matrix material 1 in step 1 and add it to saturated CO 2 The methanol solution was stirred at 500 rpm for 1 h, and after filtering, drying and sieving, the relevant powder material 2 was obtained.
[0048] Step 3, adding the powder material 2 obtained in step 2 to a nitrate solution containing Mg and Co ions for treatment, wherein the weight ratios of Mg and Co elements to the powder material are 0.006 and 0.0002, respectively, stirring at 500 rpm for 1 hour, filtering, drying and sieving to obtain a preliminary coated material 3.
[0049] Step 4, sintering the preliminary coating material 3 obtained in step 3 at 800° C. for 2 h in an atmosphere containing 50% by volume oxygen, naturally cooling to 100° C., and then sieving to obtain the Mg / Co co-coated positive electrode material 3.
[0050] Make a button cell battery.
[0051] Mg / Co co-coated cathode material 3-LiNi 0.7 Co 0.1 Mn 0.2 O 2 It is evenly mixed with conductive agent acetylene black and binder PVDF in a mass ratio of 90:3:7, and an appropriate amount of NMP is added to form a slurry. It is evenly coated on an aluminum sheet, and made into a positive electrode sheet after drying and rolling. Then, a metal lithium sheet is used as the negative electrode to assemble it into a 2032 button battery, and the electrical performance is tested using a blue electric test system (the charge and discharge voltage is 3.0~4.5V).
[0052] Example 4
[0053] Step 1: Weigh Ni at a molar ratio of Li / (Ni+Co+Mn) = 1.04. 0.6 Co 0.1 Mn 0.3 (OH) 2 Precursor and lithium oxalate, then add the precursor and lithium oxalate into a high-speed mixer, sinter the mixture at 1000° C. for 8 hours in an atmosphere containing 20% by volume oxygen, naturally cool to 100° C., and then crush and sieve to obtain a sintered matrix material 1.
[0054] Step 2: weigh the alkane matrix material 1 in step 1 and add it to saturated CO 2 The ethanol solution was stirred at 500 rpm for 1 h, and after filtering, drying and sieving, the relevant powder material 2 was obtained.
[0055] Step 3, adding the powder material 2 obtained in step 2 to a nitrate solution containing La and Y ions for treatment, wherein the weight ratios of La and Y elements to the powder material are 0.0008 and 0.002, respectively, stirring at 500 rpm for 1 hour, filtering, drying and sieving to obtain a preliminary coating material 3.
[0056] Step 4, sintering the preliminary coating material 3 obtained in step 3 at 300° C. for 2 h in an atmosphere containing 50% by volume oxygen, naturally cooling to 100° C., and then sieving to obtain La / Y co-coated positive electrode material 4.
[0057] Make a button cell battery.
[0058] La / Y co-coated positive electrode material 4-LiNi 0.6 Co 0.1 Mn 0.3 O 2 The conductive agent acetylene carbon black and the binder PVDF were evenly mixed in a mass ratio of 90:3:7, and an appropriate amount of NMP was added to form a slurry, which was evenly coated on an aluminum sheet, and made into a positive electrode sheet after drying and rolling. Then, a metal lithium sheet was used as the negative electrode to assemble a 2032 button battery 1, and the electrical performance was tested using a blue electric test system (the charge and discharge voltage was 3.0-4.5V).
[0059] Comparative Example 1
[0060] S1: Weigh Ni according to the molar ratio of Li / (Ni+Co+Mn)=1.06 0.6 Co 0.1 Mn 0.3 (OH) 2 Precursor and lithium carbonate, then the precursor and lithium carbonate are added into a high-speed mixer, the mixture is sintered at 940°C for 15h in an atmosphere containing 20% by volume of oxygen, naturally cooled to 100°C, and then crushed and sieved to obtain a sintered matrix material;
[0061] S2: Weigh the monoalkyl matrix, strontium carbonate and aluminum oxide in S1 and mix them in a high-speed mixer, wherein the weight ratios of Al and Sr elements to the powder material are 0.0006 and 0.0012 respectively. Sinter the mixture at 400°C for 2h in an atmosphere containing 50% by volume oxygen, cool naturally to 100°C, and then sieve to obtain a dry Sr / Al co-coated positive electrode material.
[0062] Make a button cell battery.
[0063] The positive electrode material LiNi 0.6 Co 0.1 Mn 0.3 O 2 It is evenly mixed with conductive agent acetylene black and binder PVDF in a mass ratio of 90:3:7, and an appropriate amount of NMP is added to form a slurry. It is evenly coated on an aluminum sheet, and made into a positive electrode sheet after drying and rolling. Then, a metal lithium sheet is used as the negative electrode to assemble it into a 2032 button battery, and the electrical performance is tested using a blue electric test system (the charge and discharge voltage is 3.0~4.5V).
[0064] Comparative Example 2
[0065] S1: Weigh Ni according to the molar ratio of Li / (Ni+Co+Mn)=1.06 0.6 Co 0.1 Mn 0.3 (OH) 2 Precursor and lithium carbonate, then the precursor and lithium carbonate are added into a high-speed mixer, the mixture is sintered at 940°C for 15h in an atmosphere containing 20% by volume of oxygen, naturally cooled to 100°C, and then crushed and sieved to obtain a sintered matrix material;
[0066] S2: Weigh the alkyl matrix material in S1 and add it to (NH 4 ) 2 CO 3 The solution was stirred at 500 rpm for 30 min, and then gradually added to a nitrate solution containing Al and Sr ions, the weight ratios of Al and Sr elements to the powder material were 0.0006 and 0.0012, respectively, and stirred at 500 rpm for 1 h. After filtering, drying and sieving, a preliminary coating material was obtained;
[0067] S3: The preliminary coating material obtained in step 3 is sintered at 400° C. for 2 h in an atmosphere containing 50% by volume oxygen, and after naturally cooling to 100° C., a Sr / Al co-coated positive electrode material is obtained by sieving.
[0068] Make a button cell battery.
[0069] The positive electrode material LiniNi is co-coated with Sr / Al by conventional wet method. 0.6 Co 0.1 Mn 0.3 O 2 It is evenly mixed with conductive agent acetylene black and binder PVDF in a mass ratio of 90:3:7, and an appropriate amount of NMP is added to form a slurry. It is evenly coated on an aluminum sheet, and made into a positive electrode sheet after drying and rolling. Then, a metal lithium sheet is used as the negative electrode to assemble it into a 2032 button battery, and the electrical performance is tested using a blue electric test system (the charge and discharge voltage is 3.0~4.5V).
[0070] The button cells of Examples 1-2 and Comparative Examples 1-2 were subjected to electrical performance tests, and the experimental data are shown in Table 1 below.
[0071] Table 1 Electrochemical performance cycle stability test results
[0072] sample 1C cycle 100 times retention rate (%) Example 1 92.2 Example 2 91.1 Comparative Example 1 87.8 Comparative Example 2 89.5
[0073] As shown in Table 1, compared with the dry coating of Comparative Example 1 and the ordinary wet coating of Comparative Example 2, the saturated CO 2 The solution is treated to form a highly uniform Li2 CO 3 Thin layer, after metal ion exchange, surface Li 2 CO 3 Transformed into amorphous Al and Sr metal ions anchored Li 2 CO 3 The coating method of the layer shows excellent cycle stability; at the same time, in the relevant saturated CO 2 Under the solution treatment coating method, the synergistic Sr / Al synergistic multi-element coating showed better cycling stability than Sr coating and Al coating.
[0074] It should be noted that, in this article, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or system including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or system. In the absence of further restrictions, an element defined by the sentence "comprises a ..." does not exclude the existence of other identical elements in the process, method, article or system including the element.
[0075] The serial numbers of the above embodiments of the present invention are only for description and do not represent the advantages or disadvantages of the embodiments.
[0076] The above are only preferred embodiments of the present invention, and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the contents of the present invention specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.
Claims
1. A method for preparing a positive electrode material for a ternary lithium-ion battery, characterized in that: The method comprises the following steps: Step 1, mixing a preset amount of ternary precursor and a Li source and sintering them in an oxygen-containing atmosphere at 700-1000° C. for 8-24 hours, crushing and sieving to obtain a sintered matrix material 1, wherein the ternary precursor is Ni x Co y Mn (1-x-y) (OH)2, 0.5≤x≤0.98, 0.01≤y≤0.3, x+y<1, the molar ratio of the lithium element in the Li source to the total molar ratio of the nickel, cobalt and manganese elements in the ternary precursor is (1.02-1.08):1; Step 2, adding the monoalkyl matrix material 1 obtained in step 1 to a carbon dioxide saturated solution and stirring and mixing for 1 to 2 hours to form a Li2CO3 layer on the surface of the monoalkyl matrix material 1, and filtering, drying and sieving to obtain a powder material 2; Step 3, adding the powder material 2 to a soluble salt solution containing metal ions and stirring and mixing for 1 to 2 hours, filtering, drying and sieving to obtain a preliminary coating material 3, wherein the weight ratio of the metal ions to the powder material 2 is (0.0002 to 0.006): 1; Step 4, sintering the preliminary coating material 3 in an oxygen-containing atmosphere at 300-800° C. for 1-6 hours, and obtaining a ternary lithium-ion battery positive electrode material uniformly coated with a metal ion compound after cooling.
2. The method for preparing the positive electrode material of a ternary lithium-ion battery according to claim 1, characterized in that: In step 1, the Li source is at least one of Li2O, LiOH, Li2C2O4 and Li2CO3.
3. The method for preparing the positive electrode material of a ternary lithium-ion battery according to claim 2, characterized in that: In step 2, the saturated carbon dioxide solution includes any one of a saturated carbon dioxide aqueous solution, a saturated carbon dioxide acetone solution, a saturated carbon dioxide methanol solution, and a saturated carbon dioxide ethanol solution.
4. The method for preparing the positive electrode material of a ternary lithium-ion battery according to claim 1, characterized in that: In step 3, the soluble salt solution includes a nitrate solution.
5. The method for preparing the positive electrode material of a ternary lithium-ion battery according to claim 1, characterized in that: In step 3, the metal ions include metal ions corresponding to metal ion carbonates having a solubility product constant lower than that of Li2CO3.
6. The method for preparing the positive electrode material of a ternary lithium-ion battery according to claim 5, characterized in that: The metal ions include at least one of metal ions corresponding to Mg, Al, Ca, Ba, Fe, Co, Mn, Cu, Zn, Y, Sr, Zr, Ce and La.
7. The method for preparing the positive electrode material of a ternary lithium-ion battery according to claim 3, characterized in that: The carbon dioxide saturated solution is a carbon dioxide acetone solution, and the Li source is lithium carbonate.
8. The method for preparing a ternary lithium-ion battery positive electrode material according to any one of claims 1 to 7, characterized in that: The oxygen-containing atmosphere in steps 1 and 4 contains 20-100% oxygen by volume.
9. A ternary lithium-ion battery positive electrode material, characterized in that: The ternary lithium-ion battery positive electrode material is prepared according to the preparation method of the ternary lithium-ion battery positive electrode material according to any one of claims 1 to 8.
10. A lithium ion battery, characterized in that: The battery comprises the ternary lithium-ion battery positive electrode material of claim 9.
Citation Information
Patent Citations
Ternary positive electrode material for zirconium-coated lithium ion battery and preparation method of ternary positive electrode material
CN111509205A
Lithium salt, positive electrode material and preparation method and application thereof
CN113086995A
Element-uniformly-coated ternary lithium ion battery positive electrode material and preparation method thereof
CN114695873A
Ternary positive electrode material with core-shell structure, preparation method of ternary positive electrode material and lithium ion battery
CN116031382A
Composite coated modified high-nickel NCA positive electrode material and preparation method therefor
WO2022267187A1